Teknik Rajut Menggunakan Benang Rajut Katun Bali Pada Ready To Wear - Ariyana Damayanti; Diah Ayu Rahmawati (Garina, 2023)
Balinese cotton knitting yarn is the main material in making knitting applications on ready to wear. The author applies knitting applications including techniques, materials, color harmony, and design. The goal is to find out how to apply the knitting technique using balinese cotton knitting yarn on ready to wear. The research method used is R&D which contains potential problems, data collection, product design, design validation, design revision, product trial, product revision, usage trial, and product revision, and descriptive data analysis. The manufacturing stages start from the design, tools and materials, tailoring, to the finishing process. The application of knitting on this ready to wear uses a hand sewing technique that is done before the sewing process, in order to get a neat result. The author also pays attention in the selection of the color of the base material that matches the knitting thread. The application of knitting applications must consider the texture of the yarn with the base material to be used, so that when applied in ready to wear it looks neat and does not seem heavy.